Differentiation of Malignant Pleural Effusions from Lung Squamous Cell Carcinoma and Adenocarcinoma through FTIR Spectroscopy: A Prognostic Approach - Madargerong, Vincentius Adrian; Suhartono, Eko; Oktaviyanti, Ika Kustiyah; Haryati, Haryati; Isa, Mohamad; Assagaf, Ali; Kusumawardhani, Erna; Nurrasyidah, Ira; Syafa’ah, Irmi (Jurnal Respirasi, 2025)
Introduction: Malignant pleural effusion (MPE) is common in cancer patients and is often caused by neoplastic involvement of the pleural surface. This study aimed to determine the utility of Fourier transform infrared spectroscopy (FTIR) spectral analysis and anatomical pathological differentiation in MPE, squamous cell carcinoma (SCC), and lung adenocarcinoma as prognostic predictors. Methods: This study used a cross-sectional design at Ulin General Hospital, Banjarmasin, involving advanced lung cancer patients with MPE. A non-probability sampling technique was used to recruit 30 patients. Fourier transform infrared spectroscopy was analyzed to evaluate anatomical pathology differentiation. Results: Differences were observed in the FTIR spectral ratios A1080/A1243 and A1080/A1170 between SCC and adenocarcinoma, with p-values of 0.026 and 0.022, respectively. Significant differences were also found in the A2959/A1545 ratio between well-differentiated and poorly differentiated adenocarcinomas, with a p-value of 0.023. The receiver-operating characteristic curve (ROC) indicated good predictive value for poorly differentiated adenocarcinoma at a cut-off value of 0.944, with a sensitivity of 50% and specificity of 100%. However, no significant correlation was found between FTIR absorbance and anatomical pathology differentiation in MPE due to SCC and lung adenocarcinoma. Conclusion: The FTIR spectral ratios A1080/A1243 and A1080/A1170 differentiate SCC from adenocarcinoma. Fourier transform infrared spectroscopy may be an adjunct to cytology, offering a more rapid and cost-effective method for differentiating MPE.